Physical Modelling Of The Steel Flow In RH Apparatus - Pieprzyca J.; Merder T.; Saternus M.; Michalek K. (Archives of Metallurgy and Materials, 2015)
The efficiency of vacuum steel degassing using RH methods depends on many factors. One of the most important are hydrodynamic processes occurring in the ladle and vacuum chamber. It is always hard and expensive to determine the flow character and the way of steel mixing in industrial unit; thus in this case, methods of physical modelling are applied. The article presents the results of research carried out on the water physical model of RH apparatus concerning the influence of the flux value of inert gas introduced through the suck legs on hydrodynamic conditions of the process. Results of the research have visualization character and are presented graphically as a RTD curves. The main aim of such research is to optimize the industrial vacuum steel degassing process by means of RH method.